Increase of efficiency of plant materials heat treatment in tubular reactors - A. V. Golubkovich; I. A. Pekhal'skiy; A. I. Dadyko; A. G. Chizhikov (Сельскохозяйственные машины и технологии)
In agriculture products of pyrolysis of plant materials in the form of waste of the main production can be applied as a source of heat and electric power. Besides, their use prevents ecological pollution of the soil and the atmosphere. Pyrolysis plants can be used for work with tubular reactors anywhere. Due to them farmers can dry grain, using waste heat of diesel generators, heatgenerators, boiler plants and receiving thus gaseous products, liquid and firm fractions. A technology based on cyclic and continuous plant mass movement by a piston in a pipe from a loading site to a place of unloading of a firm phase consistently through cameras of drying, pyrolysis, condensation of gaseous products. Exhaust furnace gases with a temperature up to 600 degrees Celsius are given countercurrent material movement from a power equipment. The gaseous, liquid and firm products from the pyrolysis camera are used for heat and electric power generation. Calculation of parameters of subdrying and pyrolysis cameras is necessary for effective and steady operation of the tubular reactor. The authors determined the speed of raw materials movement, and also duration of drying and pyrolysis in working chambers. An analysis of a simplified mathematical model of process was confirmed with results of experiments. Models of heat treatment of wet plant materials in tubular reactors are worked out on a basis of equality of speeds of material movement in the reactor and distribution of a temperature front in material on radius. The authors defined estimated characteristic for determination of tubular reactor productivity and size of heat, required for drying and pyrolysis.